Implementation of the patient safety incident guideline in district health services, Western Cape - Robert J. Mash; Kaashiefah Adamson; Abdul Isaacs; Gavin Hendricks; Jani Fouche; Jennie Morgan; Klaus von Pressentin; Lawson Eksteen; Leigh Wagner; Liezel Rossouw; Luke Profitt; Marshall Lockett; et al. (South African Family Practice)
Background: South Africa has implemented a patient safety incident reporting and learning system (PSIRLS) in 2022. The aim of this study was to evaluate the implementation of this PSIRLS in the district health services of the Western Cape.